مساهمة السياحة في النشاط الاقتصادي في مصر - خليفة، نور الهدى صفوت عوض Khalifa, Nour Alhuda Safwat Awad (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2015)
تهدف هذه الدراسة إلى بيان الأهمية الاقتصادية التي تعود على الاقتصاد المصري من النشاط السياحي والإيرادات السياحية كأحد أدوات التجارة الغير منظورة والتي تساهم في تحقيق التنمية الاقتصادية وإلى تحقيق فرص عمل والحد من البطالة، كذلك توفير موارد للدولة من النقد الأجنبي.
Domestic and international tourism activities have an important and prominent role in most of the world economies which heavily depend on it as an important source of national income. Many countries were able to achieve significant tourist revenue due to its tourist and recreational attractions and other tourist attraction factors which have an important impact on the national economy. This impact appears in the reduction of the deficit in the balance of payments and overcoming some of the economic and social problems. Thence, tourism has become closely related to the economic development; it represents, in fact, one of the most important non- commodity exports and basic element of the economic activity in different countries. Therefore, global and international organizations, such as the World Bank and the UNESCO, are concerned with tourism and consider it as an important factor of rapprochement between different cultures in the world.
Keywords: السياحة -- الايرادات السياحية -- التنمية الاقتصادية -- الاقتصاد المصري